Intention to disclose maternal HIV status to children among Chinese mothers: association with outcome expectations and moderation by perceived health - Qian Wang; Yinghui Sun; Ho Hin Lee; Kam Hei Hui; Ailing Wang; Xiaoyan Wang; Xinwei Li; Phoenix Kit-Han Mo (BMC Public Health)
Abstract Background Disclosure of maternal HIV status to children can be beneficial for both mother and children. Few studies have examined factors and moderators of HIV disclosure among mothers living with HIV. Objective The present study examined the association of outcome expectations and perceived health on intention to disclose maternal HIV status to children, and the moderating role of perceived health among women living with HIV in China. Method A cross-sectional survey was conducted among 269 women with HIV who had at least one living child aged > 5 years and had not yet disclosed their HIV status to their oldest child in China. Results Results from hierarchical regression revealed that after adjusting for significant socio-demographic and medical variables, positive outcome expectations had a positive association and negative outcome expectations had a negative association with intention to disclose HIV. Perceived health had no significant association with intention to disclose HIV. Furthermore, a significant moderation effect of perceived health on positive outcome expectations was found. Further analysis showed that the association of positive outcome expectations and intention to disclose HIV was stronger among women with better perceived health. Conclusion Findings support the importance of outcome expectations, and the need to consider the moderating role of perceived health on HIV disclosure among women living with HIV in China.